Exploring The Practice Of Enterprise Architecture In Universiti Utara Malaysia : A Case Study - Sibsi, Mohamed Nasir (2008)
Alignment between business and information technology (IT) remains on the top-ten lists of concerns. Enterprise architecture (EA) provides an approach and guidance for enabling better alignment. The purpose of EA is to more effectively align the strategies of enterprises with processes and resources (IT and business). The research problem addressed by this study was lack of alignment between business strategy and IT strategy, leading to increased costs and loss of competitive advantage. The objective of this study was to identify how EA practice in UUM, evaluate and finally recommendations for achievement of better business-IT alignment enabled by enterprise architecture. Thus, the study conducted several interview, questionnaire and survey. The data collected was analyzed based on four EA factors such as business, application, technical and technology architecture.